“El petróleo es de Colombia y para los colombianos”: la huelga de 1948 en Barrancabermeja y la reversión de la Concesión de Mares (2013)
The goal of this paper is to analyze the strike performed by workers from oil workers’  union (USO) in 1948 against Tropical Oil Company. From a theoretical view of  Collective Action Theory (TAC) was made this work and enhance aspects like political  opportunities for strike, solidarity and the result of confrontation. In the same way, the  national and regional press is used to show how strike is developing. In this way, we  want to show the strike was a specific demonstration of the fight for nationalizing the  Colombian oil against the monopolist capital.